Influencia del excesivo uso de las redes sociales en relaciones interpersonales de estudiantes de 3er año de la Institución Educativa Víctor Raúl Haya de la Torre-2018. - García Rubio, Rosa María (2019)
This research was carried out at the Víctor Raúl Haya de la Torre Educational Institution with the third year “A” and “B” high school students in the El Porvenir District, with the purpose of analyzing the influence of excessive use of social networks in interpersonal relationships. The research was based on methods, quantitative and qualitative techniques where a population of 39 students was worked between men and women; which contributed to gathering relevant information about the problem investigated. For the study of this problem in the research, the problematic reality is made known, as well as the variables to be studied under the approach of the problem, the hypotheses and objectives on which the research is based, in turn, theoretical approaches are exposed , the results obtained that reaffirm the research are shown so that social networks negatively influence students by damaging interpersonal relationships, poor communication within the classroom and behind a screen, in turn in the analysis and discussion of Results show the impact of the use of Facebook in each of the students who, through testimonies, reaffirm each of the questions applied in the questionnaire. Also, the conclusions and recommendations of all the research carried out are presented.